The Show-and-Tell War - Smith, Janice Lee (New York Harper and Row, 1988)
Five stories relate the adventures and misadventures of Adam Joshua as he contends with the first day of school, pretending to be sick, stealing a library book, making the scariest Halloween costume, and being upstaged at show-and-tell time.
Keywords: Children Literature